A Model of Consumer-Based Brand Equity (CBBE) for Global Fashion Brand - Ekinci, Yuksel; Molinillo-Jiménez, Sebastián; Japutra, Arnold (University of Zaragoza, 2017)
This study’s aims are twofold. Firstly, to assess the external validity of Yoo and Donthu's (2011) and Nam et al.’s (2011) brand equity model and a retail brand equity model in the retail industry in Spain. Secondly, to advance Nam et al.’s (2011) CBBE model by introducing brand awareness and brand trust. The study contributes to the branding literature in two ways: (1) comparing validity of three CBBE brand equity models in a different culture and advancing understanding of brand equity dimensions and their relationships with brand satisfaction, brand trust and brand loyalty in the fashion retail industry.
Keywords: Moda - Marcas registradas; Brand loyalty; Consumer-based brand equity; Brand trust; Fashion retail industry; Global brand